Characterization of endogenous and exogenous mouse mammary tumor virus proviral DNA with site-specific molecular clones. - Groner, B (1980)
Restriction fragments of the mouse mammary tumor virus (MMTV) proviral DNA were obtained by molecular cloning procedures. A 4-kilobase fragment delimited by two PstI sites was isolated from unintegrated, linear MMTV DNA and amplified in the pBr322 plasmid vector. EcoRI fragments of proviral DNA, integrated into the genome of a GR mammary tumor cell line, were isolated as lambda recombinant molecules. Five different recombinant phages which contained the 3' region of the MMTV proviral DNA and adjacent host DNA sequences were isolated. Heteroduplex analysis and S1 nuclease digestion suggested that there is no extensive sequence homology in the host DNA flanking the different proviral genes. The cloned DNA was fractionated into site-specific restriction fragments which served as molecular probes in the analysis of the endogenous MMTV proviral copies of C3H, GR, BALB/c, and feral mice. This allowed the correlation of MMTV-specific EcoRI fragments obtained from genomic DNA of these strains with the 5' and 3' ends of the proviral gene. Restriction fragments of two clones which contained the proviral sequences adjacent to the flanking host DNA as well as 1 to 2 kilobases of host DNA were used as hybridization probes, and the results allow the following conclusions: the proviral DNA of both clones contains nucleotide sequences complementary to the 5' and 3' ends of proviral DNA; and the host DNA flanking one clone belongs to the unique class of genomic DNA, whereas the DNA flanking the second clone is reiterated at least 15 times within the mouse genome.